The Impact of Environmental Social Governance Performance, Debt to Equity Rasio, and Corporate Social Responsibility Disclosure on Return on Asset - Fanny Pemudi Rukmana; Devyanthi Syarif (eCo-Fin, 2026)
This study examines the effects of environmental social governance performance, debt to equity ratio, and corporate social responsibility disclosure on the return on assets of Indonesian apparel and luxury goods companies between 2017 and 2024. Employing a quantitative approach that adopts a descriptive and verificative approach, the study looks at 56 financial statements from specific apparel and luxury goods companies. The correlations between the variables were evaluated using analysis of multiple linear regression, the coefficient of determination test, traditional assumption tests, as well as the product moment correlation coefficient test such as t-tests and F-tests for assessing hypotheses. The data was processed utilizing SPSS 21.0. According to the test findings that are not complete, ROA is positively impacted by ESG Performance and CSR Disclosure but not by DER. However, the simultaneous test findings show that ESG Performance, DER, and CSR Disclosure taken have a major influence when combined.on Return On Asset. According to these results, activity ESG performance, DER, and CSRD mix are more important factors in determining Return On Asset in the apparel and luxury goods business than short-term solvability.